CongoFlux – The First Eddy Covariance Flux Tower in the Congo Basin - Sibret, Thomas; Bauters, Marijn; Bulonza, Emmanuel; Lefevre, Lodewijk; Cerutti, Paolo Omar; Lokonda, Michel; Mbifo, José; Michel, Baudouin; Verbeeck, Hans; Boeckx, Pascal (Frontiers in Soil Science, 2022)
The Congo basin is home to the second-largest tropical forest in the world. Therefore, it plays a crucial role in the regional water cycle, the global carbon cycle and the continental greenhouse gas balance. Yet very few field-based data on related processes exist. In the wake of global change, there is a need for a better understanding of the current and future response of the forest biome in this region. A new long-term effort has been set up to measure the exchange of greenhouse gasses between humid lowland tropical forest in the Congo basin and the atmosphere via an eddy-covariance (EC) tower. Eddy-covariance research stations have been used for decades already in natural and man-made ecosystems around the globe, but the natural ecosystems of Central Africa remained a blind spot. The so-called “CongoFlux” research site has been installed right in the heart of the Congo Basin, at the Yangambi research center in DR Congo. This introductory paper presents an elaborated description of this new greenhouse gas research infrastructure; the first of its kind in the second-largest tropical forest on Earth.